2012
DOI: 10.1038/eye.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between specially trained and accredited optometrists and glaucoma specialist consultant ophthalmologists in their management of glaucoma patients

Abstract: Aims Optometrists are becoming increasingly involved in the co-management of glaucoma patients as the burden on the Hospital Eye Service continues to escalate. The aim of this study was to assess the agreement between specially trained optometrists and glaucoma-specialist consultant ophthalmologists in their management of glaucoma patients. Methods Four optometrists examined 23-25 patients each and the clinical findings, up to the point of dilation, were documented in the hospital records. The optometrist, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…It has demonstrated that community based optometrists with a special interest in glaucoma (OSI) can effectively reduce the number of unnecessary referrals attending the hospital glaucoma service in low risk patients 9. Good agreement between the examination findings of a specialist optometrist in glaucoma and the hospital were reported with this and other schemes before the National Institute for Health and Clinical Excellence (NICE) glaucoma guidelines were published in April 2009 6 7 9 11 12. The publication of the NICE guidelines prompted a recommendation from the Association of Optometrists (AOP) to refer all patients with an IOP of greater than 21 mm Hg regardless of the method of measurement 20 21…”
Section: Introductionmentioning
confidence: 97%
“…It has demonstrated that community based optometrists with a special interest in glaucoma (OSI) can effectively reduce the number of unnecessary referrals attending the hospital glaucoma service in low risk patients 9. Good agreement between the examination findings of a specialist optometrist in glaucoma and the hospital were reported with this and other schemes before the National Institute for Health and Clinical Excellence (NICE) glaucoma guidelines were published in April 2009 6 7 9 11 12. The publication of the NICE guidelines prompted a recommendation from the Association of Optometrists (AOP) to refer all patients with an IOP of greater than 21 mm Hg regardless of the method of measurement 20 21…”
Section: Introductionmentioning
confidence: 97%
“…Similar schemes of optometrist involvement in the investigation or management of glaucoma have been reported elsewhere, notably Bristol, Manchester, Carmarthenshire, Portsmouth and Huntingdon. 2,[9][10][11][12][13][14][15] In some instances, optometrists work within hospital glaucoma clinics alongside a consultant-led service. In other cases, specially trained community optometrists are used within a referral-refinement process whereby the optometrist acts as an intermediary between the community optometrist referral and entry into the hospital eye service, designed to filter out falsepositive referrals.…”
Section: Introductionmentioning
confidence: 99%
“…There are long-standing UK precedents for the development of specialist optometrists in contact lenses and orthoptics and, more recently, in therapeutics 132 and glaucoma. 133,134 However, the process of establishing a specialist qualification for optometrists is lengthy, requiring the drafting of a syllabus, core competencies, training programmes and assessment procedures. 135 The viability of a specialist qualification should be a topic for further research.…”
Section: Practitioner Dependentmentioning
confidence: 99%